Unlawful Means in Primary Investigation - Karkoush, Mustafa (PROSPECTIVE RESEARCHES, 2024)
In this research, we dealt with illegal means in the primary investigation. The research problem was entitled to what extent are the texts of the Iraqi legislator sufficient to regulate illegal means in the primary investigation? In this research, the researcher adopted the analytical approach and also used the comparative approach in some places. For this reason, the researcher divided the research into two requirements. In the first requirement, we dealt with what is the nature of interrogation and the accused, and in it we discussed the concept of interrogation and the identity of the accused. In the second requirement, we addressed the illegal means of interrogation. In the first section, what are the illegal methods, and in the second section, the illegal methods in interrogation? At the end of the research, we concluded a set of results and recommendations that serve the research